Comparison of Guideline‐Directed Medical Therapy in Black versus White Patients With Heart Failure With Reduced Ejection Fraction in a Large, Integrated Health Care System - Natalia C. Berry; Yi‐Shin Sheu; Karen Chesbrough; R. Clayton Bishop; Suma Vupputuri (Clinical Cardiology, 2026)
ABSTRACT Background Guideline‐directed medical therapy (GDMT) improves clinical outcomes for patients with heart failure with reduced ejection fraction (HFrEF). While GDMT treatment differences have been described for Black patients, data are limited. Aims We sought to evaluate, among Black and White HFrEF patients, differences in GDMT use and target dosing by race. Materials & Methods We examined health records of Black and White patients with HFrEF between 2015 and 2022. GDMT was defined by four medication classes—ACEi/ARB/ARNi, beta blocker (BB), mineralocorticoid receptor antagonist (MRA), and SGLT2i. Proportions of patients on GDMT and achieving target dose were examined for each class. Logistic regression was used to assess variables associated with differential GDMT use and dosing. Results Our cohort totaled 2825 HFrEF patients (61.2% Black; 38.8% White). Compared to White patients, Black patients had higher treatment with ACEi/ARB/ARNi (84.1% vs. 80.0%), BB (85.3% vs. 74.9%), and MRA (27.9% vs.18.4%), but similar SGLT2i treatment. Among treated, Black patients were more likely to be treated to target with ACEi/ARB/ARNi (45.2% vs. 34.2%), BB (25.0% vs. 17.8%), and MRA (80.3% vs. 72.1%). After multivariate adjustment, MRA treatment was associated with race (OR = 1.39; 95% CI: 1.10–1.75). Among treated, Black patients had higher odds of treatment to target with ACEi/ARB/ARNi (OR = 2.0; 95% CI: 1.61–2.53) and MRA (OR = 1.6; 95% CI: 1.01–2.57). Conclusions Using real‐world data from a diverse health system, we demonstrated that Black patients had 2.0 times and 1.6 times greater odds of being treated to target with ACEi/ARB/ARNi and MRAs, respectively, compared to White patients. Future research should explore whether these differences translate to improved health outcomes.